KAIDAH KEBAHASAAN DALAM TEKS KUMPULAN PANTUN ADAT MELAYU SAMBAS KARYA NAHARI - Hakim, Lukman Nul; Wartiningsih, Agus; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to find out the elements of linguistic rules that build the pantun text, see and know the forms of tradition and culture in the Sambas Malay community which is reflected in the pantun text. The general problem in this study is "What are the language rules in the Sambas Malay customary text collection?" The general problem is divided into specific sub-topics, namely "(1) rhyme, (2) diction, (3) image form, (4) figuratively, (5) implementation in learning? "The theory in this study relates to the structure and rules of rhyme. The methodology applied is descriptive qualitative form. Obtaining data is done by documentary study techniques. There are 40 pantun data. The data source of the research is a collection of poetry texts which contains a description of the culture of the Sambas Malay community and data collection tools such as stationery, recording cards, and laptops. The results of this study are (1) rhymes with vowel and consonant suffixes, (2) Choice of words that include general, special, ancient word choices. (3) The form of pengimaji in rhymes which includes the form of tradition and culture of the Sambas Malay community. (4) figurative words.  Keywords: traditional pantun, language rules, sambas community culture.